Um estudo do processo de desenvolvimento de uma sequência temática crítico transformadora com foco na produção, exibição e divulgação de audiovisuais sobre questões energéticas no mundo com alunos do ensino médio - (:unkn) unknown (Universidade Estadual de Goiás, 2016)
Is investigated in this research paper the process of production of critical-transformers audiovisual, for high school students on the issues of energy, from the perspective of the relations Science, Technology, Society and Environment (CTSA), assuming as an educational assumption the critical design -transformadora and liberation of Paulo Freire. We then ask that assume a critical stance to overcome the technical design and antropocentrada the use of technologies to other progressive epistemological. This allowed us to add the production of critical transformers audiovisual-to-FREIRE CTSA joint, defined by Auler (2002), obtaining FREIRE-CTSA liaison with Audiovisual Production Manufacturing Critical (FREIRE-CTSAAVCT). We expect that this combination will allow us to understand why an audiovisual production process can help to ensure that students participate in decision making in order to overcome the myths created about Science and Technology. In support Theoretical Methodological Research, we will use participatory research, defined by Rose (2013), considering its progressive character, within the qualitative perspective of sociological research. Thus, this research could dialogue with the problematical educational proposal of Paulo Freire (1987) and the CTSA approach, intended to identify the potential social contradictions of the reality experienced by the subjects-objects of research in order to achieve social transformation thereof . As didactic and pedagogic purpose of this work, we have built a thematic sequence, using the relationship between the Textual Analysis Discourse and the Thematic Research, defined by Torres, et. al. (2008) (ATD-IT). This coordination enabled us to recognize, analyze and interpret the social contradictions experienced by students in order to obtain the generator theme, which is the energy in the world, and we select the critical content required for building the critical and transformative ST, referring to teaching Science / Physics.
Keywords: Ensino de física; Tecnologia da informação - Comunicação; Audiovisual crítico transformador; Relações ciências; Tecnologia, sociedade e ambiente (CTSA); Ensino médio; Physics education; Information - Communication technology; Audiovisual production critical manufacturing; Science relations; Technology; Society and environment (CTSA); High School; EDUCACAO::ENSINO-APRENDIZAGEM; ENSINO-APRENDIZAGEM::TECNOLOGIA EDUCACIONAL